Exploring the curvilinear relationship between corporate social performance and financial performance: Evidence from South African listed firms - Van Niekerk, Michael-John (Department of Finance and Tax, 2024)
In the past, there has been a wealth of research into the relationship between corporate social performance (CSP) and corporate financial performance (CFP). However, this relationship has not been thoroughly researched in developing markets, particularly in South Africa. Compelling theoretical arguments and empirical evidence have been presented both for and against the financial benefits associated with CSR. Recently, there has been an increasing number of studies attempting to reconcile these seemingly opposing views by suggesting that the CSP-CFP relationship may in fact be non-linear. This study aims to contribute to this perspective and address the research gap in South Africa by exploring the shape of the CSP-CFP relationship in a South African context. This is achieved through the use of panel regression models with fixed and random effects, on an overall CSP and component CSP level for 130 Johannesburg Stock Exchange (JSE) listed firms from 2012 to 2019 (1 040 firm-year observations). Bloomberg ESG disclosure scores are used as a proxy for CSP and its components (environmental performance, social performance, and governance performance). CFP is proxied through a measure of market-based performance, annual shareholder return (ASR), and a measure of accounting-based performance, return on assets (ROA). A significant U-shaped relationship is found between overall CSP and CFP. This same relationship is also found between environmental performance and CFP, and between social performance and CFP. Contrary to the findings of prior South African studies, a negative linear relationship is found between governance performance and CFP. The findings of this study have implications for managers facing increasing pressure to engage in environmental, social, and governance (ESG) initiatives from investors and the broader public, and for researchers in emerging markets to explore the CSP-CFP relationship from a novel perspective.